Diagnostic Value of IGFBP-1 Rapid Test and Combined IGFBP-1-AFP in Vaginal Fluid from Premature Rupture of Amniotic Membranes - Aryati, Aryati; Kusumawati, Lulut; Sulistyono, Agus (Indonesian Socety of Obstetrics and Gynecology, 2015)
Objective: To compare the diagnostic value of IGFBP-1 and combined IGFBP-1-AFP rapid tests in diagnosing premature rupture of membranes (PROM). Method: This study was conducted in Dr. Soetomo Hospital in Surabaya from July to November 2013. The subjects were 52 pregnant women with presumed PROM diagnosis, which was recorded by clinical data and sampling of vaginal discharge swab. The diagnostic value was obtained by comparing the results of IGFBP-1 and combinated IGFBP-1-AFP rapid tests by standard PROM examination namely vaginal pooling, litmus paper test and ferning test. Result: A difference between the diagnostic value of IGFBP-1 and combined IGFBP-1-AFP rapid tests in diagnosing PROM was shown, where the sensitivity and specificity of IGFBP-1 rapid test was 85% and 95%, compared to combined IGFBP-1-AFP rapid test, which was 91% and 95%. The correlation coefficient of combined IGFBP-1-AFP rapid test with standard PROM examination (r=0.841, p=0.000) was higher than the correlation coefficient of IGFBP-1-AFP rapid test with standard PROM examination (r=0.772, p=0.000). Conclusion: Combined IGFBP-1-AFP rapid test has a better diagnostic value than IGFBP-1 rapid test alone. Keywords: combined IGFBP-1-AFP, IGFBP-1, PROM